Potential of voids to enhance natural ventilation in Medium Cost Multi-Storey Housing (MCMSH) for hot and humid climate - Muhsin, Fakhriah; Mohammad Yusoff, Wardah Fatimah; Mohamed, Mohd Farid; Mohamamd Raani, Mohammad Rasidi; Sapian, Abdul Razak (Asian Research Publishing Network, 2017)
The objective of this study is to discuss the potential of voids in Medium Cost Multi-Storey Housing (MCMSH) for hot and humid climate. The result has a significant to identify the suitable configurations of voids for better passive design strategy. In this study, the performance of voids for MCMSH has been studied by using CFD simulation. This study provides a result of different configurations of voids for the studied buildings. The results suggest the appropriate parameter that affects the enhancement of natural ventilation for MCMSH to be adapted in hot and humid climate. The discussion forms a basic framework of void’s proportions in MCMSH to serve better environmental living environment for the MCMSH’s occupants.